The Networks in Encouraging Women to Start and Sustain Businesses: Systematic Literature Review - Hifzhan Frima Thousani; Mochammad Heri Edy (Universitas Muhammadiyah Palu, 2023)
Entrepreneurship is a driving force for global economic growth, with women increasingly recognized for their substantial contributions to innovation, job creation, and overall prosperity. This research employs a Systematic Literature Review (SLR) methodology, ensuring a thorough and unbiased exploration of existing knowledge. Providing crucial insights into women's entrepreneurship dynamics, the study underscores that robust managerial skills enhance the likelihood of women forming familial business partnerships. However, pervasive gender discrimination poses a significant hurdle, potentially steering women towards independent ventures. Early-stage female entrepreneurs heavily rely on familial and governmental support, particularly from husbands, alongside access to business knowledge, shaping their ventures profoundly. The dynamic landscape faced by women entrepreneurs is influenced by various factors that can either facilitate or impede success. This study emphasizes the key role of managerial skills while acknowledging gender discrimination as a formidable obstacle, underscoring the need for addressing these challenges in fostering inclusive entrepreneurial ecosystems.